Analisis Pengaruh Kualitas Layanan Terhadap Loyalitas Pelanggan Dengan Kepuasan Dan Kepercayaan Pelanggan Sebagai Variabel Intervening Pada Asuransi Jiwa Manulife Indonesia-Surabaya - Steven Darwin (Jurnal Strategi Pemasaran, 2014)
The purpose of this research are to know : (1) Influence of service quality (reliability, responsiveness, assurance, emphaty, tangible) to Customer Satisfaction, Trust, and Loyalty Manulife Indonesia in Surabaya. (2) Influence of Customer Satisfaction and Trust to Customer Loyalty Manulife Indonesia in Surabaya.            This research is taken 100 consumers of Manulife Indonesia while data is collected by using questionnaire. Analysis technique use Structural Equation Modeling (SEM) and processed using software AMOS version 16.0.            The result shows there are significant correlation between service quality to customer satisfaction, trust and not significant correlation between customer loyalty and there is significant correlation between customer satisfaction and trust to customer loyalty.